“PENGARUH KUALITAS PELAYANAN DAN KOMUNIKASI PEMASARAN TERHADAP KEPUASAN PELANGGANSMARTFRENDI KOTA MALANG” - Muhammad Afifi Rahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The development of both information and communication technology requires consumers to increase the intensity in everyday life, because today is in dire need of various elements in the provision of information services and telecommunications.The purpose of this study was the effect of the variable determines the quality of service and marketing communication to customer satisfaction modem Smartfren in Malang.In this study, analyzed the influence of the variable quality of service that consists of items: physical evidence (tangibles), reliability (reliability), assurance (assurance), responsiveness (responsiveness) and empathy (empathy) and variable marketing communication consists of items: advertising ( advertising), personal selling (personal selling), sales promotion (sales promotion), public relations (public relations), as well as direct marketing (direct marketing) to customer satisfaction modem Smartfren in Malang. The study sample was taken by using purposive sampling of 100 consumers who use products such as smartphones Smartfren (mobile phones) and a modem. This study used a survey method explanatory research. The data collection techniques using questionnaires, library research, internet browsing, and interviews. Then, after the data is collected, the sorting is done by analyzing the data followed using a Likert scale, then test the validity and reliability, and for clicking-use tools such as crosstabs statistical software SPSS 16.0.From the research that has been done, the results showed that based on the results of multiple linear regression analysis using the F test (simultaneous) it can be concluded simultaneously affect customer satisfaction, then the t-test results it can be concluded that partially affect customer satisfaction, and based on the results of the regression coefficient (standardized Beta Coefficients), respectively, it is known marketing communications variable dominant influence on customer satisfaction modem Smartfren in Malang. Thus, the effect of service quality and marketing communications simultaneously, partial and dominant influence customer satisfaction. Keyword; Service Quality, Marketing Communications, Customer Satisfaction